RECICLAGEM DE ÓLEO COMESTÍVEL E FABRICAÇÃO DE SABÃO COMO INSTRUMENTOS DE EDUCAÇÃO AMBIENTAL - Wildner, Loreni Beatriz Arnold; Hillig, Clayton (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704243 This study has as main objective to investigate the level of understanding of 32 professionals whowork at the Municipal School Children Copetti Solange Ana, a member of the municipal school ofIjuí on pollution caused by improper disposal of waste edible oil. It was found that the monthlyconsumption varies, and consumes 44% of group 2 to 3 liter and 13% consume 3 to 4 liters, and41% of these consumers discard a relatively large amount, more than one liter per month. Themodes of disposal are variable, and 9% put directly into the sink, the soil has 12%, 25% anddonates 41% saved for soap, put in 4% and 9% trash reused to make food for animals or make firein grill. Additionally we sought to educate the group about the main consequences of improperdisposal, (soil sealing, water contamination and methane gas production, responsible for thegreenhouse effect), through awareness lecture and workshop manufacture of soap. Also soughtbe formed environmental multipliers, aiming to disseminate environmental information andpromote engagement in the struggle for a healthy and balanced environment.